The longitudinal association between multiple cardiometabolic diseases, socioeconomic status, and depressive symptoms in China - Dan Guo; Yanshang Wang; Yanan Zhao; Ruoxi Ding; Yanan Luo; Wanwei Dai; Ping He (Scientific Reports)
Abstract The aim of this study is to investigate the effect of cardiometabolic diseases (CMDs) on the development of depressive symptoms and to determine whether socioeconomic status (SES) moderates this effect. A total of 6,455 individual free from depressive symptoms were selected from the China Health and Retirement Longitudinal Study (CHARLS). CMDs and SES were self-reported. Depressive symptoms were assessed using the Center for Epidemiologic Studies Depression Scale (CESD-10). Cox proportional hazards regression models were employed to examine the association between baseline CMDs and subsequent depressive symptoms. Stratified analysis were conducted to explore the moderating effect of SES on this association.Participants with any CMDs exhibited a higher risk of developing depressive symptoms compared to those without CMDs, with a hazard ratio (HR) of 1.10 (95% CI: 1.01, 1.20). Individuals with one CMD (HR = 1.08, 95% CI: 1.00, 1.20) or cardiometabolic multimorbidity (HR = 1.13, 95% CI: 1.02, 1.26) also demonstrated an increased risk. The effect of CMDs on depressive symptoms was observed primarily in adults aged 60 years and older with lower education attainment (HR = 1.28, 95%CI: 1.12, 1.46), lower income (HR = 1.29, 95%CI: 1.11, 1.50) and rural residency (HR = 1.29, 95%CI: 1.12,1.51). These findings emphasize the importance of closely monitoring the mental status of patients with CMDs and considering routine screening and evaluation for depressive symptoms, especially in individuals with low SES.